Seasonal and spatial variations of saltmarsh benthic foraminiferal communities from North Norfolk, England - Saad, Salha A.; Wade, Christopher M. (Springer Verlag, 2016)
Time series foraminiferal data were obtained from samples collected from three sites at Brancaster Overy Staithe, Burnham Overy Staithe and Thornham on the North Norfolk coast over a 1-year period. At each collection point, six environmental variables—temperature, chlorophyll, sand, mud, pH and salinity—were also measured. The principle aim of this study was to examine the benthic foraminiferal fauna in regard to the temporal variability of foraminiferal abundance, seasonal trend, dominant species, species diversity and the impact of environmental variables on the foraminiferal communities in the top 1 cm of sediment over a 1-year time series. The foraminiferal assemblages at the three sites were dominated by three species: Haynesina germanica, Ammonia sp. and Elphidium williamsoni. Foraminiferal species showed considerable seasonal and temporal fluctuation throughout the year at the three investigated sites. The foraminiferal assemblage at the three low marsh zones showed a maximum abundance in autumn between September and November and a minimum abundance observed between July and August. There were two separate peaks in the abundance of Ammonia sp. and E. williamsoni, one in spring and another in autumn. In contrast, H. germanica showed a single peak in its abundance in autumn. A generalized additive modelling approach was used to explain the variation in the observed foraminiferal abundance and to estimate the significant impact of each of the environmental variables on living foraminiferal assemblages, with taxa abundance as the dependent variable. When included in the model as predictors, most of the environmental variables contributed little in explaining the observed variation in foraminiferal species abundance. However, the hypotheses for differences amongst sites, salinity and pH were significant and explained most of the variability in species relative abundance.